The Wednesday wars - Schmidt, Gary D. (New York : Sandpiper ; Houghton Mifflin, 2007)
"During the 1967 school year, on Wednesday afternoons when all his classmates go to either Catechism or Hebrew school, seventh-grader Holling Hoodhood stays in Mrs. Baker's classrooom, where they read the plays of William Shakespeare and Holling learns much of value about the world he lives in." -- T.p. verso.
Accelerated Reader AR
Newbery Honor, 2008.
Keywords: Shakespeare, William, -- 1564-1616. -- Juvenile fiction; Shakespeare, William, -- 1564-1616. -- Fiction; Bildungsromans -- Juvenile fiction; Junior high schools -- Juvenile fiction; Schools -- Juvenile fiction; Families -- New York (State) -- Long Island -- Juvenile fiction; Coming of age -- Fiction; Junior high schools -- Fiction; Schools -- Fiction; Family life -- New York (State) -- Long Island -- Fiction; Long Island (N.Y.) -- History -- 20th century -- Juvenile fiction; Long Island (N.Y.) -- History -- 20th century -- Fiction; New York (State) -- Fiction; Bildungsromans